2015
DOI: 10.15420/aer.2015.4.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rotors in the Ablative Therapy of Persistent Atrial Fibrillation

Abstract: Catheter ablation is more effective than pharmacological therapy for the secondary prevention of patients with paroxysmal 1,2 and persistent 3,4 atrial fibrillation (AF) and has an emerging role in the primary prevention of paroxysmal AF. 5,6 Nevertheless, in randomised clinical trials (RCTs) its success in treating patients with paroxysmal AF is 40-60 % for a single procedure and 70 % for multiple procedures at one year, 1,2 and results for persistent AF are lower. 7,8 Thus, there is an urgent unmet need to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Second, the time period that fibrillatory conduction can sustain AF without driver is still questionable. It may last from seconds to hours . It is still unclear how localized ablation effects on RoAc and what mechanisms lead to the termination of AF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the time period that fibrillatory conduction can sustain AF without driver is still questionable. It may last from seconds to hours . It is still unclear how localized ablation effects on RoAc and what mechanisms lead to the termination of AF.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, NavX (St. Jude Medical, St Paul, MN, USA) 3‐D electroanatomic mapping system was used. RoAc was defined as sustained clockwise or counterclockwise activation around a core, or a centrifugal activation from an origin, which were located on the basis of their electrode coordinates . The basket coverage was confirmed in all cases by fluoroscopy and/or ICE, electrograms quality checking and basket visualization on the 3‐D mapping system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that not all possible PS hotspots are identified during a single AF episode, motivating the methodology of Boyle et al (2019) that identifies different driver locations through different AF initiation protocols. Narayan et al (2012) demonstrated high success rates by ablating focal and re-entrant drivers identified through phase and activation mapping of basket catheter data (Schricker and Zaman, 2015). Ensuring the correct classification of phase singularities is critical for targeting ablations because wavefront break up does not represent an equal target to a stable rotor.…”
Section: Electrical Ablation Approachesmentioning
confidence: 99%